Fibroblast growth factor-23 and the risk of cardiovascular diseases and mortality in the general population: A systematic review and dose-response meta-analysis - Liu, Menglu; Xia, Panpan; Tan, Ziqi; Song, Tiangang; Mei, Kaibo; Wang, Jingfeng; Ma, Jianyong; Jiang, Yuan; Zhang, Jing; Zhao, Yujie; Yu, Peng; Liu, Xiao (Frontiers in Cardiovascular Medicine, 2022)
Background: In the past decade, FGF23 has been recognized as an important biomarker of cardiovascular diseases. This study aimed to assess the relationship between fibroblast growth factor 23 (FGF23) and the risk of cardiovascular diseases (CVDs) in general populations. Methods: The protocol was registered prospectively in PROSPERO (CRD42021281837) and two authors independently searched for relevant studies in the PubMed, EMBASE, and Cochrane Library databases. Results: In total, 29 prospective studies involving 135,576 participants were included. In the general population, the category analysis revealed that elevated FGF23 levels were related to increased risks of myocardial infarction (MI) (RR: 1.40, 95%CI: 1.03-1.89), stroke (RR: 1.20, 95%CI: 1.02-1.43), heart failure (HF) (RR: 1.37, 95%CI: 1.23-1.52), CVD events (RR: 1.22, 95%CI: 0.99-1.51), cardiovascular mortality (RR: 1.46, 95%CI: 1.29-1.65), and all-cause mortality (RR: 1.50, 95%CI: 1.29-1.74). In the continuous analysis, per doubling of FGF23 was associated with increased risks of MI (RR:1.08, 95%CI: 0.94-1.25), stroke (RR:1.21, 95%CI: 0.99-1.48), HF (RR:1.24, 95%CI: 1.14-1.35, CVD events (RR: 1.12, 95%CI: 0.99-1.27), cardiovascular mortality (RR: 1.43, 95%CI: 1.09-1.88), all-cause mortality (RR: 1.37, 95%CI: 1.15-1.62). Furthermore, the dose-response analysis demonstrated a potentially nonlinear relationship between FGF23 and stroke, HF, and all-cause mortality. In contrast, a potentially linear relationship between FGF23 and cardiovascular mortality was observed (p for nonlinearity =0.73). Conclusion: The present study suggests that increased serum FGF23 levels are positively related to CVD events and mortality in the general population. The clinical application of FGF23 levels to predict CVD risk requires further research.